2013
DOI: 10.1093/mnras/stt124
|View full text |Cite
|
Sign up to set email alerts
|

Hot accretion flow in black hole binaries: a link connecting X-rays to the infrared

Abstract: Multiwavelength observations of Galactic black hole transients have opened a new path to understanding the physics of the innermost parts of the accretion flows. While the processes giving rise to their X-ray continuum have been studied extensively, the emission in the optical and infrared (OIR) energy bands was less investigated and remains poorly understood. The standard accretion disc, which may contribute to the flux at these wavelengths, is not capable of explaining a number of observables: the infrared e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(151 citation statements)
references
References 136 publications
(181 reference statements)
7
142
2
Order By: Relevance
“…In the above modeling, the OIR fluxes are dominated by the reprocessed emission from the outer edge of the disk at =Ŕ 4.4 10 out 11 cm, where the temperature is »1 eV. Using the radial dependence of the temperature in the irradiated disk, µ -T r irr 3 7 (Cunningham 1976; Veledina et al 2013), we estimate the disk temperature at the launching point to be »7 times larger than that at R out . To investigate whether the reprocessed emission from the disk around the wind launching radius can explain the opposite behavior of the OIR and X-ray fluxes, we add a bbodyrad component with a temperature of 7 eV to the model for MJD 53446 and compare it with the SED at the Chandra epoch.…”
Section: Sed Fits For the Chandra Epoch In The Hypersoft Statementioning
confidence: 98%
See 1 more Smart Citation
“…In the above modeling, the OIR fluxes are dominated by the reprocessed emission from the outer edge of the disk at =Ŕ 4.4 10 out 11 cm, where the temperature is »1 eV. Using the radial dependence of the temperature in the irradiated disk, µ -T r irr 3 7 (Cunningham 1976; Veledina et al 2013), we estimate the disk temperature at the launching point to be »7 times larger than that at R out . To investigate whether the reprocessed emission from the disk around the wind launching radius can explain the opposite behavior of the OIR and X-ray fluxes, we add a bbodyrad component with a temperature of 7 eV to the model for MJD 53446 and compare it with the SED at the Chandra epoch.…”
Section: Sed Fits For the Chandra Epoch In The Hypersoft Statementioning
confidence: 98%
“…In this condition, the disk height increases at larger radii in proportion to r 9 7 due to heating by irradiation. Ther 12 7 dependence was recently adopted to model multiwavelength SEDs in the low/hard state (Veledina et al 2013). Also, previous irradiated disk models describe the strength of the reprocessed component with one parameter F out (the fraction of illuminating flux thermalized in the outer disk), while optxrplir separates it, for the convenience of calculation, into two explicit parameters: the geometrydependent factor, f out , and ( ) -a 1 out , where f out is the height of the disk at the outer edge divided by the outer radius and a out is the albedo of the outer disk.…”
Section: The Optxrplir Modelmentioning
confidence: 99%
“…The range of wavelengths where the hot flow emits is determined by its size: the larger is the truncation radius of the cold accretion disc, the lower is the frequency where synchrotron radiation is still not absorbed. The self-absorption (turnover) frequency is (Veledina et al 2013a)…”
Section: Hot Accretion Flowmentioning
confidence: 99%
“…For the radial dependences B ∝ R −β and τ ∝ R −θ the self-absorption frequency scales as νt ∝ R −[β(p+2)+2θ]/(p+4) and the total OIR spectrum from a hot flow is composed of contributions of synchrotron peaks (in partially opaque regime) coming from different radii. The hot flow spectrum constitutes a power-law with the spectral index (Veledina et al 2013a)…”
Section: Hot Accretion Flowmentioning
confidence: 99%
“…An alternative explanation came from Veledina et al (2011Veledina et al ( , 2013, who suggested that the optical emission is produced by synchrotron emission in a magnetised, extended hot accretion flow (for a detailed review of this model, see Poutanen, this volume). A possible caveat to this otherwise promising model is the need for a very large (hundreds of gravitational radii) outer radius of the hot inflow, which is not compatible with what other observations seem to suggest about the location of the X-ray power-law emission and the disc truncation radius (e.g.…”
Section: Bhxrbs: Oir Reveals Non-thermal Variabilitymentioning
confidence: 99%